Nepalko Saikshik Parampara: Prambhadekhi Tribhuvan Vishwovidhyalayako Sthapanasamma - Chalise, Pushpa Raj (Tribhuvan University Journal, 2010)
Not available. Key words: Education system; T.U.; Nepal Tribhuvan University Journal Vol. XIX, 1996 Page: 173-181 Uploaded Date: 24 Nov., 2010